Local community perception towards the place identity of The Royal Mausoleum of Sultan Mahmud Shah, Kota Tinggi, Malaysia - Mohd Nashir, Nur Shahida Nasha; Ismail, Mohd Hafizal (2019)
The Royal Mausoleum of Sultan Mahmud Shah is a small and mundane heritage landmark in the Historical Tourism District in Johor. The Royal Mausoleum represents the history of Sultan Mahmud Shah II, which his decease remarked the end of the glorious dynasty of Melaka Sultanate in Johor ruling system. It is realized through the inheritance of history of the deceased Sultan Mahmud Shah and the symbolic of the Royal Mausoleum as a heritage asset in Kota Tinggi creates an identity among the local community towards the place. This research aimed to identify the identity and value of cultural heritage among community in relation to the existence of Royal Mausoleum at Kota Tinggi, Johor using an adopted model by Breakwell’s Theory on Identity which emphasized on continuity, distinctiveness, and self-esteem. Quantitative method is used based on questionnaire survey conducted to 300 respondents in order to measure the dependency of the place and local identity of the community. Analysed using t-test and ANOVA analysis, the results showed that there was an emotion bonding and memory attachment to the Royal Mausoleum among the local community in the village. The Royal Mausoleum seems to bring back the nostalgia in terms of old memories especially among the veteran group of local community. The results confirmed that the socio-demographic background such as education, occupation, and age group mostly influenced the significance of items for place identity, which were ‘distinctiveness’ and ‘self-esteem’. This research contributed in identifying the place identity of the Royal Mausoleum. Hence, it helped in strengthen the criteria of the Royal Mausoleum to be more presentable as tourist attraction.